Migrating Fictions : Twentieth-Century Internal Displacements and Race in U.S. Women's Literature - Manzella, Abigail G. H. (Book collections on Project MUSE., 2018)
In Migrating Fictions, Manzella turns to U.S. Women's literature that represents internal migrations in the US in the twentieth century. This project situates itself within the "spatial turn" of literary studies to analyze the way the U.S has displayed a history of spatial colonization, which we see as a pattern we turn to a variety of seemingly disconnected forced migrations. With chapters that focus on migrations related the Dust Bowl, the Great Migration, the migration of peoples placed in Japanese American internment camps, and the migration of Southwestern migrant labor, Manzella makes some fascinating connections across narratives that would not typically be brought together. Ultimately, this project lays bare the oppressive practices of U.S. policy and reveals the resistance individual groups accessed as they completed these internal migrations.